Spectra, Electronic structure, Biological activities and Molecular docking investigation on methyl (2E)-2-{[N-(2-formylphenyl)-4-methyl benzene sulfonamido] methyl}-3-(naphthalen-1-yl) prop-2-enoate: an experimental and computational approach. (2019) - Vetrivelan, V.
Abstract: The title compound methyl (2E)-2-{[N-(2-formylphenyl)-4-methyl benzene sulfonamido] methyl}-3-(naphthalen-1-yl) prop-2-enoate (MFMNPE) is a derivative of sulfonamide. Molecular structure and vibrational analysis of MFMNPE has been carried out by experimental and theoretical approaches. The NBO analysis using theoretical (DFT) method confirms the description of electronic delocalization of the compound. HOMO and LUMO energies make certain that charge transfer takes place within the molecule. Additionally global chemical reactivity descriptors (chemical hardness, total energy, electronic chemical potential and electrophilicity) are calculated for MFMNPE and accustomed predicts their relative stability and reactivity. All the calculations were administrated by B3LYP/6-311++G (d, p) method. The in vitro antimicrobial activity of the compound reveals that it exhibits antimicrobial activity against the several microorganisms. Molecular docking studies concede that MFMNPE could exhibit 1KE4 inhibitor activity.